2022-RA-1130-ESGO Effect of imiqiumod treatment on HLA-G expression in high-grade cervical lesions. (20th October 2022) - Cokan, Andrej; Henrique da Silva, Neila Caroline; de Oliveira, Sheilla Andrade; Kavalar, Rajko; Pakiž, Maja; But, Igor; Lucena-Silva, Norma
Abstract : Introduction/Background: We showed that the topical application of the 5% imiquimod in treating cervical high-grade squamous intraepithelial lesions (HSIL) leads to a regression of about 50% of the lesions after 16 weeks of treatment (1). Tissue culture studies have attributed imiquimod's antiviral and antitumor activity to the enhancement of the innate immune response. Knowing that the increase in soluble HLA-G (sHLA-G) expression is associated with disease progression and that the HLA-G molecule has an inhibitory effect on different immune cells, we further investigated whether imiquimod modulates the sHLA-G expression in the cervical lesions. Methodology: Cervical biopsies of 52 patients aged 18–40 with histological HSIL (CIN2p16+ and CIN3), who self-applied 250 mg cream containing 5% of imiquimod three times a week for 16 weeks, were collected at admission and after completion of the treatment. Treatment success was defined as the absence of HSIL after treatment. For immunohistochemistry, we used the monoclonal anti-HLA-G antibody (Exbio, 5A6G7) ( figure 1 ). The intensity of pixels obtained from the images of the slides, using the program Gimp 2.10.18, defined the protein levels ( figure 2 ). We used the T-test to compare two groups, the ROC curve to define the cut-off point for risk-predicting sHLA-G expression, and the Fisher's exact test to calculate the risk. Results: High tissue sHLA-G levels before treatment were associated with unsuccessful imiquimod treatment (p=0.0025). Imiquimod down-modulated sHLA-G in the lesion of those successfully treated (p=0.0467) or not (p<0.0001). According to the area under the curve of 0.72, 95%CI 0.61–0.84, p=0.0012, sHLA-G expression over 870847 pixels represented a 4-fold risk for unsuccessful imiquimod treatment (p=0.0088). Conclusion: We showed that imiquimod modulates HLA-G in cervical lesions and that treatment success depends on sHLA-G levels at admission.